P659 Colonoscopic screening of symptomatic patients suggests an emerging inflammatory bowel disease (IBD) in urban and rural south India. (27th May 2021) - Banerjee, R; Pal, P; Tevethia, H; Ganesh, G; Chandayapeta, J; Adigopula, B; Mudigonda, S; Reddy, D N
Abstract: Background: Recent studies suggest that IBD is on the rise in the developing world. This is also the region with limited access to healthcare facilities, poor physician and patient awareness of the disease and diagnostic dilemmas with the infectious bacterial diarrheas preventing adequate diagnosis. There is very limited data on the relative prevalence of IBD compared to the infectious diarrhoeas. We screened symptomatic patients to assess the diagnostic profile in the real world settings with free of cost service to people below poverty line and the un-insured. Methods: The study is being conducted in a large tertiary care centre in Southern India from March 2020 till date. We present the results of an interim analysis. Symptomatic patients with diarrhea, unintentional weight loss, bleeding per rectum, chronic abdominal pain and unexplained anemia were screened with a blood test (Haemogram, liver function, serum protein), abdominal ultrasound and colonoscopy/ileoscopy to ensure an early diagnosis and initiation of treatment. Data including the demographics of the patients, predominant symptoms, rural/urban residence, investigations, biopsy and final diagnosis were entered into an excel spreadsheet and analysed. Results: 6878 patients, 2188 female (32%), median 44 years (1–82 years) were screened between March 2020 to January 2021. Bloody diarrhoea was noted in 1212(18%), chronic non-bloody diarrhoea in 887 (13%), altered bowel habits in 2381 (35%), pain abdomen in 4030 (59%), un-intentional weight loss in 648 (10%) and anemia in188 (3%). IBD was diagnosed in 397 patients (6%) of which 169 (2.5%) were UC and 228 (3.3%) were CD. Infective etiology including intestinal tuberculosis was seen in 577 (8.3%). Colorectal cancer was diagnosed in 251 (3.6%), polyps in 614 (8.9%). Overall, 4921 (71.5%) were urban and 1957 (28.5%) rural. The proportion of UC (2.3% rural vs 2.5% urban, p=0.65) and CD (3.6% rural and 3.2% urban, p=0.43) were not different in rural and urban groups. There was significantly higher proportion of infectious colitis in the rural subgroup (p=0.01)(Table 1). Conclusion: This interim analysis indicates a rising IBD in both urban and rural India vis a vis the infectious diarrheas. However, proportion of infectious colitis was significantly higher in the rural subgroup compared to the urban.